Significance of image-defined risk factors for surgical complications in patients with abdominal neuroblastoma - Günther, Patrick; Holland-Cunz, Stefan; Schupp, Christine Johanna; Stockklausner, Clemens; Hinz, Ulf; Schenk, Jens-Peter (European journal of pediatric surgery, 2011)
Neuroblastoma (NB) is one of the most common malignant tumors in infancy. The commonly used International Neuroblastoma Staging System is not suitable for determining the surgical risks. To address this, we aimed to evaluate the correlation between so-called image-defined risk factors (IDRFs) and the surgical risks in abdominal neuroblastoma. We evaluated 60 cases who underwent surgical intervention and examined the pre-surgical radiological imaging to look for IDRFs and surgical complications in children with abdominal neuroblastoma. The MRI- and CT-scans showed a total of 122 IDRFs in 39 cases. Complete resection was carried out in 50%, partial excision in 32%, and biopsy in 18% of cases. Total resection was possible in 100% of cases with no IDRF. Where IDRFs were present, total resection was only possible in 26% of cases (p<0.0001). We found a highly significant, negative correlation between the number of IDRFs and the possibility of performing complete resection of NB (p<0.0001). 7 (11.6%) complications were detected, all in patients who showed at least one IDRF previously. Our findings indicate that IDRFs are useful indicators for predicting surgical risk and surgical outcome and thus should be taken into account when planning surgery.
Gesehen am 20.07.2022